Morpheme {buN-}: an Example of Morphological Process through Affixation in Bidayuh-Somu Language - Bunau, Eusabinus; Yusof, Rohani Mohd (Lingua Cultura, 2018)
The goals of this research were to identify the allomorph of morpheme {buN-}, describe its affixation process, and determine the function of the allomorphs. The qualitative method was applied to gather the data from an informant who was done by recording technique on the field research. The informant was a Bidayuh-Somu language native speaker. The collected data included the derivational words derived from free morpheme that was root, base, and bound morpheme. The free and bound morpheme were then sorted into nominal and verbal class, as well as described qualitatively. Affixation as one of the morphological processes to derive complex derivational word in Bidayuh-Somu Language involved free and bound morpheme. Morpheme {buN-} was chosen as an example to describe the process of affixation in deriving complex derivational word of the language. It is found that the morpheme {buN-} is a prefix and verbal, affixed to the verb, and noun and adjective. Therefore, it functions both as class-maintaining and class-changing. Moreover, it is identified that the morpheme {buN-} has five allomorphs, namely /bu-/ with its alternant /bur-/ and /b-/, and /bum-/, /bun-/, /buN-/ and /bu-/. The morpheme {buN-} is affixed to free morpheme which is initiated with all consonant and vowel phonemes. The morpheme buN-also bears meanings